S11 = 11/2 (2a+10d)
so plug and chug
The first term of an A.P is 2 and it's common difference is 3, find the sum of the first 11 terms of the A.P
2 answers
The sum of the first n terms of the A.P :
S(n) = n / 2 [ 2 a1 + ( n - 1) d ]
In this case:
a1 = 2 , d = 3 , n = 11
S(11) = 11 / 2 [ 2 ∙ 2 + ( 11 - 1 ) ∙ 3 ]
S(11) = 5.5 ( 4 + 10 ∙ 3 )
S(11) = 5.5 ( 4 + 30 )
S(11) = 5.5 ∙ 34
S(11) = 187
S(n) = n / 2 [ 2 a1 + ( n - 1) d ]
In this case:
a1 = 2 , d = 3 , n = 11
S(11) = 11 / 2 [ 2 ∙ 2 + ( 11 - 1 ) ∙ 3 ]
S(11) = 5.5 ( 4 + 10 ∙ 3 )
S(11) = 5.5 ( 4 + 30 )
S(11) = 5.5 ∙ 34
S(11) = 187